PENGARUH KOMUNIKASI DAN MOTIVASI TERHADAP EFEKTIVITAS KERJA PEGAWAI DI KANTOR KECAMATAN ASEMBAGUS KABUPATEN SITUBONDO - Zain, Muh Hamdi; Basuki, Eddy (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Abdurachman Saleh Situbondo, 2023)
The low performance of the employees of Asembagus sub-district office, Situbondo district in carrying out their duties during this time, the impact on the low quality and quantity of work employees in carrying out the main tasks and functions. Based on the background, the researchers conducted research related to the influence of motivation and communication on the performance of employees of the foundation. This type of research uses a quatitative research approach. Based on the results of the study concluded that: 1). Motivation affects the performance of employees in carrying out their work duties. 2). Communication affects the performance of employees in carrying out their work duties. Based on the above conclusions, there is no difference between the initial hypothesis and the results of the study. In the hypothesis that has been written at the beginning, it is said that motivation and communication have an influence on performance